Comparing three forms of early intervention for youth with borderline personality disorder (the MOBY study): study protocol for a randomised controlled trial. Issue 1 (December 2015) - Chanen, Andrew; Jackson, Henry; Cotton, Sue; Gleeson, John; Davey, Christopher; Betts, Jennifer; Reid, Sophie; Thompson, Katherine; McCutcheon, Louise
Abstract Background Borderline personality disorder is a severe mental disorder that usually has its onset in youth, but its diagnosis and treatment are often delayed. Psychosocial 'early intervention' is effective in improving symptoms and behaviours, but no trial has studied adaptive functioning as a primary outcome, even though this remains the major persistent impairment in this patient group. Also, the degree of complexity of treatment and requirements for implementation in mainstream health services are unclear. The primary aim of this trial is to evaluate the effectiveness of three forms of early intervention for borderline personality disorder in terms of adaptive functioning. Each treatment is defined by combining either a specialised or a general service delivery model with either an individual psychotherapy or a control psychotherapy condition. Methods/design The study is a parallel-group, single-blind, randomised controlled trial, which has randomised permuted blocking, stratified by depression score, sex and age. The treatments are: (1) the specialised Helping Young People Early service model plus up to 16 sessions of individual cognitive analytic therapy; (2) the Helping Young People Early service plus up to 16 sessions of a control psychotherapy condition known as 'befriending'; (3) a general youth mental health care model plus up to 16 sessions of befriending. Participants will comprise 135 help-seeking youth aged 15–25 years with borderline personality disorder. After baseline assessment, staff blind to the study design and treatment group allocation will conduct assessments at 3, 6, 12 and 18 months. At the 12-month primary endpoint, the primary outcome is adaptive functioning (measures of social adjustment and interpersonal problems); secondary outcomes include measures of client satisfaction, borderline personality disorder features, depression and substance use. Discussion The results of this trial will help to clarify the comparative effectiveness of a specialised early intervention service model over and above general youth mental health care, along with the contribution of individual cognitive analytic therapy over and above specialised general clinical care in early intervention for borderline personality disorder. Consequently, the findings will also inform the level of training and competency required for effective delivery of early intervention services. Trial registration Registered with the Australian New Zealand Clinical Trial RegistryACTRN12610000100099 on 1 February 2010.